Current trends in forestry research of Latin-America: An editorial overview of the Special Issue - Martínez Pastur, Guillermo José; Roig Junent, Fidel Alejandro (Ecological Processes)
Mendoza city (Argentina) hosted the VIII Latin American Forestry Congress (CONFLAT) and the V Forestry Congress of Argentina (CFA) in 2023, where relevant issues were addressed, such as climate change, degradation, reforestation, management and forest industry, monitoring, environmental services, social issues, and governance, among others. The objective of this Special Issue was to present the main advances in Forestry Science for Latin-America in the context of changing governance and forest livelihoods for people. The fifteen articles emphasize the interdisciplinary nature of the forest management and conservation, and that multiple variables must be considered to achieve sustainability. The articles come from studies across Southern South-America (Argentina, Brazil, Chile, and Uruguay), and the collaboration of researchers of other countries (México, Canada, and Spain). Articles include research in tropical, Mediterranean and temperate Sub-Antarctic forests. Together, these articles provide a snapshot of new forestry research carried out locally and internationally to bring about beneficial ecological and environmental outcomes in a world facing the challenges of sustainable management and conservation amongst the threats and uncertainty of climate change and environmental degradation responsible for extensive loss of biodiversity and environmental services. We believe that this Special Issue will encourage more inter-disciplinary research focusing on management and conservation of forests. Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Roig Junent, Fidel Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de ...